"As their waistlines recede": Tracing and challenging the fat quest in young adult literature. Issue 2 (2nd July 2016) - Shelton, Sarah A.
ABSTRACT: The author argues that both authors and critics of young adult literature must challenge the ableist discourse determining and surrounding "positive" fat protagonists. She analyzes and critiques Jean Webb's celebration of the " Bildungsroman of weight loss" and claims that, far from being positive, such plot structures meld the quest with the cosmetic panopticon to produce "the fat quest, " a culturally constructed set of steps a fat protagonist must take before he or she can be considered human, thin, and worthy enough of narratives thin teen protagonists enjoy by default. Outlining the fat quest, the author then analyzes several books from the 21st century that frustrate, challenge, or abandon it. Finally, she argues for more novels that subvert the fat quest in order to help teens find true body-positivity.